Review of the Nomada roberjeotiana species-group (Hymenoptera: Apidae) of Russia, with description of new species - Proshchalykin, Maxim Yu.; Lelej, Arkady S. (Zootaxa, 2010)
The twelve species and two subspecies of Nomada roberjeotiana species-group from Russia are reviewed. Two new species, Nomada mitaii sp. nov. (Russia, Mongolia), and N. setteri sp. nov. (Russian Far East) are described and illustrated. A female lectotype is designated for Nomada palmeni Morawitz 1888. Nomada esana Tsuneki 1973 and N. hakusana hakusana Tsuneki 1973 are recorded for the first time from Russia. Nomada rufipes Fabricius 1793 is newly recorded from the Russian Far East and Kazakhstan, and N. roberjeotiana roberjeotiana is newly recorded from Mongolia. The distribution data for other species are enlarged. An identification key is presented for both sexes of this species-group.